Simultaneous overexpression of ∆6-, ∆12- and ∆9-desaturases enhanced the production of γ-linolenic acid in Mucor circinelloides WJ11 - Wang, Xiuwen; Yang, Junhuan; Mohamed, Hassan; Shah, Aabid Manzoor; Li, Shaoqi; Pang, Shuxian; Wu, Chen; Xue, Futing; Shi, Wenyue; Sadaqat, Beenish; Song, Yuanda (Frontiers in Microbiology, 2022)
Mucor circinelloides WJ11, an oleaginous filamentous fungus, produces 36% lipid of its cell dry weight when cultured in a high C/N ratio medium, however, the yield of γ-linolenic acid (GLA) is insufficient to make it competitive with other plant sources. To increase the GLA content in M. circinelloides WJ11, this fungus was engineered by overexpression of its key genes such as Δ6-, Δ12-, and Δ9-desaturases involved in GLA production. Firstly, we tried to overexpress two Δ6-desaturFull methodologies were inserted to the manuscriptase isozymes to determine which one played important role in GLA synthesis. Secondly, Δ6- and Δ12-desaturase were co-overexpressed to check whether linoleic acid (LA), the precursor for GLA synthesis, is a limiting factor or not. Moreover, we tried to explore the effects of simultaneous overexpression of Δ6-, Δ12-, and Δ9-desaturases on GLA production. Our results showed that overexpression (1 gene) of des61 promoted higher GLA content (21% of total fatty acids) while co-overexpressing (2 genes) des61 and des12 and simultaneous overexpressing (3 genes) des61, des12, and des91 increased the GLA production of engineered strains by 1.5 folds and 1.9 folds compared to the control strain, respectively. This study provided more insights into GLA biosynthesis in oleaginous fungi and laid a foundation for further increase in GLA production in this fungus.